Improved Chiral SFC Screening for Analytical Method Development. Issue 11 (15th August 2013) - Schafer, Wes; Chandrasekaran, Tilak; Pirzada, Zainab; Zhang, Chaowei; Gong, Xiaoyi; Biba, Mirlinda; Regalado, Erik L.; Welch, Christopher J.
ABSTRACT In this study we describe the evaluation of a recently developed supercritical fluid chromatography (SFC) instrument for automated chiral SFC method development. The greatly improved gradient dwell volume and liquid flow control of the new instrument in combination with the use of shorter columns containing smaller stationary phase particles affords chiral SFC method development that is faster and more universal than previous systems. Chirality 25:799–804, 2013. © 2013 Wiley Periodicals, Inc.